Phosphoramidite ligand design for the enantioselective conjugate addition of alkylzirconium reagents to enones - Roth, PMC (2014)
The development of new methods to make carbon-carbon bonds asymmetrically remains a challenge in organic chemistry. Indeed, the development of highly selective methods often proceeds on a trial and error basis. The way chiral information is transferred to the substrate is unclear in many reactions, limiting further development. We focus here on developing an asymmetric conjugate addition of alkylzirconium nucleophiles to Michael acceptors. The development of new phosphoramidite ligands, supported by a computer based model, allowed further development of the reaction. First, existing methods to introduce enantioselectively chirality are described. Then we discuss ligands, and modern ways to parameterise experimental data using computational methods. In chapter two, after discussing the use of alkenes as reagents, especially processes initiated by hydrometallation, we describe a new conjugate addition reaction using cyclic enones that achieves both high yields and levels of enantioselectivity. In chapter three, various applications of phosphoramidite ligands are discussed and we describe the synthesis of a variety of different phosphoramidites and identification of important structural features of these ligands. New, efficient ligands are obtained and a computer model is developed to account for the selectivity of the reaction discussed in chapter two. Chapter four describes the development of an enantioselective synthesis of quaternary centres with novel ligands used to optimise the new system. Lastly, chapter five describes the extension of the method to some linear enones, using different ligands. Overall, we have developed a variety of ligands which were used to expand the enone scope of a conjugate addition and an understanding of what factors make these ligands effective.